Hippocampus Cytoarchitecture and Diseases - Zhang, Xinhua (IntechOpen, 2022)
The hippocampus is a bicortical structure with extensive fiber connections with multiple brain regions. It is involved in several functions, such as learning, memory, attention, emotion, and more. This book covers various aspects of the hippocampus including cytoarchitecture, functions, diseases, and treatment. It highlights the most advanced findings in research on the hippocampus. It discusses circuits, pattern formation process of grid cells, and zinc dynamics of the hippocampus. The book also addresses the tau pathology and circRNAs related to Alzheimer's disease and potential treatment strategies. It is a useful resource for general readers, students, and researchers.